2022
DOI: 10.1155/2022/5398157
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-Sequencing Reveals the Active Involvement of Macrophage Polarizations in Pulmonary Hypertension

Abstract: Background. Sustained hypoxia can trigger a progressive rise in pulmonary artery pressure and cause serious pulmonary diseases. Macrophages play important roles along the progression of pulmonary hypertension. However, the state of macrophage polarization during the early stage of pulmonary hypertension is unclear. Methods. Unlike traditional sequencing method, single-cell sequencing can accurately distinguish among cell types and better understand cell-to-cell relationships. In this study, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Macrophages have remarkable phenotypic plasticity that enables them to efficiently respond to a variety of stimuli by generating three macrophage populations that can be broadly categorized as classically activated (M1), alternatively activated (M2), and anti-inflammatory (regulatory) macrophages [ 11 ]. Of these subtypes, M2 macrophages were reported to be involved in the development of PH and other lung disorders due to their ability to promote fibrosis, injury repair and angiogenesis [ 12 ]. Furthermore, recent studies demonstrated that the recruitment of alternatively activated macrophage in the early stages of PH were critical for later PVR [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages have remarkable phenotypic plasticity that enables them to efficiently respond to a variety of stimuli by generating three macrophage populations that can be broadly categorized as classically activated (M1), alternatively activated (M2), and anti-inflammatory (regulatory) macrophages [ 11 ]. Of these subtypes, M2 macrophages were reported to be involved in the development of PH and other lung disorders due to their ability to promote fibrosis, injury repair and angiogenesis [ 12 ]. Furthermore, recent studies demonstrated that the recruitment of alternatively activated macrophage in the early stages of PH were critical for later PVR [ 13 ].…”
Section: Introductionmentioning
confidence: 99%